Penjelasan Dokter dan Durasi Pengambilan Obat terhadap Loyalitas Pasien BPJS dengan Variabel Kepuasan Pasien sebagai Variabel Intervening (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of a doctor's explanation and duration of drug intake on BPJS patient loyalty, with patient satisfaction as an intervening variable. The research method used cross-sectional. The results showed that there was an effect of doctor's explanation on BPJS patient loyalty at RSU Royal Prima Medan P value